Learning Community Management in Improving the Quality of Learning in Elementary Schools - Cecep Jaenudin; Maman Suherman (Journal of Science and Education (JSE), 2025)
The underutilization of school learning communities in improving learning quality and teacher competence is still a concern. This study explores planning, organizing, implementing, and evaluating learning communities at SD Negeri Galudra and SD Negeri Manangga Sumedang (April 9–16, 2025) using observation, interviews, and documentation.Findings indicate a strong link between rising Education Report scores and effective management. The program works through four stages. Planning includes forming teams, setting goals, commitments, strategies, schedules, and budgets. Organization builds resilient teams, assigns responsibilities, and establishes structures. Implementation involves analyzing Education Report results, studying the Pancasila Student Profile (P5), developing P5 modules, and holding open learning activities. Supervision/Evaluation is done through reflection, group assessment, and follow-up plans. Overall, the learning community is managed effectively, though challenges remain in commitment and time coordination. The solution is reinforcing shared responsibility and arranging short, regular schedules to ensure continuity amidst busy routines.